Analisis determinan terhadap Length of Stay (LoS) di ruang isolasi Covid-19 RSUD Jend. A. Yani Kota Metro - Devina Harti Syaputri; Dian Ratih Laksmitawati; Prih Sarnianto; Andreas Infianto (Universitas Islam Indonesia, 2023)
Abstract Background: The increasing incidence of Coronavirus Disease 2019 (COVID-19) in Indonesia affects the need for hospital inpatient services. One of the parameters of service quality and the use of hospital resources is the length of stay (LOS).Objective: To find the determinants of COVID-19 that affect LOS in hospitals.Methods: Retrospective observational data collection using a cross-sectional study design. The sampling method used was total sampling during the January-August 2021 hospitalization period in the Isolation Room of the General Hospital of Jend. A. Yani Metro City. The data used is medical record data. Bivariate analysis uses Chi Square, while multivariate analysis uses Multiple Logistics Regression.Results: The sample consisted of 443 patients who were treated during the period January-August 2021 in the COVID-19 isolation room at RSUD Jend. A. Yani Metro City. The median LOS is 6 days. Multiple logistic regression analysis shows that the determinants of LOS include severity, diabetes mellitus, heart disease, and D-Dimer.Conclusion: Severity, comorbid diabetes mellitus, comorbid heart disease, and D-Dimer value are the determinants of LOS in confirmed COVID-19 patients in the COVID-19 isolation room at General Ahmad Yani Hospital, Lampung Province.Keywords: Determinants, Coronavirus Disease, LOS, hospital Intisari Latar belakang: Angka kejadian Coronavirus Disease 2019 (COVID-19) yang mengalami peningkatan di Indonesia mempengaruhi kebutuhan layanan rawat inap rumah sakit. Salah satu parameter mutu layanan dan penggunaan sumber daya rumah sakit adalah length of stay (LOS).Tujuan: Untuk mencari determinan COVID-19 yang berpengaruh terhadap LOS di rumah sakit.Metode: Pengambilan data secara retrospektif observasional menggunakan desain studi cross sectional. Metode pengambilan sampel menggunakan total sampling selama periode rawat Januari-Agustus 2021 di Ruang Isolasi RSUD Jend. A. Yani Kota Metro. Data yang digunakan adalah data rekam medis. Analisis bivariat dengan menggunakan Chi Square, sedangkan analisis multivariat menggunakan Regresi Logistik Ganda.Hasil: Sampel berjumlah 443 pasien yang di rawat selama periode Januari-Agustus 2021 di ruang isolasi COVID-19 RSUD Jend. A. Yani Kota Metro. Median LOS adalah 6 hari. Analisis regresi logistik ganda menunjukkan bahwa determinan LOS meliputi; tingkat keparahan, diabetes mellitus, penyakit jantung, D-Dimer.Kesimpulan: Tingkat keparahan, komorbid diabetes mellitus, komorbid penyakit jantung, nilai D-Dimer merupakan determinan terhadap LOS pasien COVID-19 terkonfirmasi di ruang isolasi COVID-19 RSUD Jenderal Ahmad Yani Provinsi Lampung.Kata kunci: Determinan, Coronavirus Disease, LOS, rumah sakit